UV Phototransistors-Based upon Spray Coated and Sputter Deposited ZnO TFTs - Kumar, Dinesh; Gomes, Tiago Carneiro [UNESP]; Alves, Neri [UNESP]; Fugikawa-Santos, Lucas; Smith, Graham C.; Kettle, Jeff (Institute of Electrical and Electronics Engineers (IEEE), 2020)
A comparison of Zinc Oxide (ZnO) phototransistors prepared by spray and sputter coating process is presented. The work shows that spray coated layers provide significant advantages in sensor response over ZnO phototransistors made by physical vapour deposition and we show that spray deposited ZnO phototransistors can exhibit state-of-the-art performances for UV photodetectors. Topographic images of the samples surface shows that there is increase in surface roughness in spray coated samples indicating increasing grain sizes, which is considered the source of the greater sensor responsivity. X-ray photoelectron spectroscopy (XPS) is also used to understand the root cause of the greater UV responsivity. It was observed that sprayed ZnO TFTs are more sensitive to UV radiation due to higher adsorption of oxygen level. Responsivity and external quantum efficiency (EQE) of the sprayed and sputtered ZnO TFTs are also evaluated.
Keywords: detector; Flexible; radio frequency sputtering; spray coating; TFT; ultraviolet light; ZnO